2021
DOI: 10.1371/journal.pmed.1003418
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and costs of publicly funded patient navigation interventions to enhance HIV care continuum outcomes in the United States: A before-and-after study

Abstract: Background In the United States, patients with HIV face significant barriers to linkage to and retention in care which impede the necessary steps toward achieving the desired clinical outcome of viral suppression. Individual-level interventions, such as patient navigation, are evidence based, effective strategies for improving care engagement. In addition, use of surveillance and clinical data to identify patients who are not fully engaged in care may improve the effectiveness and cost-effectiveness of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…PHEs leveraged their social capital, empathy, and personal experience to recruit participants for the program and support their retention in care. While an ample body of evidence shows the value of peer navigation in HIV services (20)(21)(22)(23), our research adds nuance to the existing literature by pro ling the multifaced roles that PHEs served for primarily Latina, transgender, immigrant participants; addressing their needs for gender a rming care, information around immigration, and bilingual services from primarily Latinx staff. Navigation in Triunfo encompassed case management, peer counseling and education, and both in-clinic and external service navigation.…”
Section: Discussionmentioning
confidence: 89%
“…PHEs leveraged their social capital, empathy, and personal experience to recruit participants for the program and support their retention in care. While an ample body of evidence shows the value of peer navigation in HIV services (20)(21)(22)(23), our research adds nuance to the existing literature by pro ling the multifaced roles that PHEs served for primarily Latina, transgender, immigrant participants; addressing their needs for gender a rming care, information around immigration, and bilingual services from primarily Latinx staff. Navigation in Triunfo encompassed case management, peer counseling and education, and both in-clinic and external service navigation.…”
Section: Discussionmentioning
confidence: 89%
“…To date, several interventions have been developed to improve PrEP uptake and adherence among Black/African American MSM, [17][18][19][20] but far fewer interventions have been developed to improve PrEP persistence. Although patient navigation is a commonly used approach for improving care engagement among people living with HIV infection, [32][33][34] it is less often implemented in the context for improving care engagement among people accessing PrEP. Several recent studies have demonstrated the benefits of patient navigation programs in improving PrEP initiation.…”
Section: Discussionmentioning
confidence: 99%
“…In several jurisdictions, HIV surveillance information is used by local health departments as a means of systematically identifying patients who were never in care after their diagnosis with HIV infection, who recently disengaged in care, or who are at high risk for disengaging from care for patient navigators to locate and attempt to link or relink them or keep them engaged. 32,[41][42][43] Use of these data allow for efficient allocation of limited patient navigation resources to those most in need of their services. In this study, the PrEP navigator benefited from the use of near real-time data on pharmacy purchases to quickly identify patients at high risk of experiencing gaps in care or disengaging from care entirely because of problems acquiring medication.…”
Section: Discussionmentioning
confidence: 99%
“…Because this individualized approach to support was key to this pilot's success, further research is recommended to understand the financial feasibility of this individualized approach for long term and larger scale programs. This recommendation was similarly made by Shade et al [36], who in their review of 16 PN interventions across the United States found that among these interventions (all of them taking place over 11-12 months) most of their intervention costs went towards providing tailored support to patients at the individual level [36].…”
Section: Sustainability Of Pn Programsmentioning
confidence: 93%